Consequences of elder abuse and neglect among older adults in rural Malaysia / Raudah Mohd Yunus - Raudah, Mohd Yunus (2018)
Elder Abuse and Neglect (EAN) is a growing public health concern. With the rapid increase of older population worldwide and especially in developing countries, EAN is likely to escalate. Abuse in late life has been shown to cause various adverse health impacts. However, compared to the other two domains of family violence – child abuse and intimate partner violence (IPV) – research findings pertaining to EAN health consequences are relatively scarce. This study is divided into two phases. Phase I is a systematic review that seeks to gather and critically appraise all the existing evidence on the health consequences of EAN. Phase II is a two-year prospective cohort study that aims at investigating the longitudinal relationships between EAN and three outcomes: mortality, sleep quality and chronic pain. A total of 1927 older adults in Kuala Pilah, Negeri Sembilan were recruited through a multi-stage cluster sampling strategy and interviewed face-to-face at baseline. One thousand one hundred and eighty nine (1189) were followed-up two years later through phone calls. Mortality was tracked using data from the National Registration Department. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI) and chronic pain was ascertained by self-reports consisting of two validated questions. Findings from Phase I ranked premature mortality, depression and anxiety as the most credible health outcomes of EAN. In Phase II, survival analysis and Cox regression showed no statistically significant difference of mortality risks between EAN victims and those not abused (β: 0.26, p=0.25), but patterns of hazard and survival plots suggested greater hazard and lower survival for EAN victims. A short follow-up period was a possible reason for statistical non-significance. With regards to sleep quality, abuse victims had significant worsening iv of sleep over the period of two years compared to their non-abused counterparts (β: 0.49, p=<0.01). Among the EAN subtypes, neglect and psychological abuse were identified as stronger contributors to poor sleep: neglect (β: 1.13, p=0.03), psychological abuse (β: 0.64, p=<0.01). On the other hand, EAN did not contribute to higher risks of developing chronic pain (β: 1.14, p=0.45). In conclusion, abuse in late life adversely affects health. Preventive and intervention measures to address this problem need to be carried out at multiple levels: individual, community, healthcare, larger environment and system. Scientific evidence related to other health impacts of EAN is still scarce, thus highlighting the need for more research.